PARENTAL INTERACTIONS AND CYBERBULLYING ON PSYCHOLOGICAL IMPACT OF HIGH SCHOOL ADOLESCENTS IN SUMBERSARI DISTRICT, JEMBER: Interaksi Orangtua dan Paparan Cyberbullying Terhadap Dampak Psikologis Remaja SMA di Kecamatan Sumbersari Kabupaten Jember - Alkatiri, Shalsabiila; Rukmini Devy, Shrimarti; Ubaidillah, Nanda Iskandar (Universitas Airlangga, 2024)
Background: The National Survey stated 45% of 2,777 Indonesian youths had experienced cyberbullying, including harassment via chat applications (45%), distribution of personal documentation (41%) and other harassment (14%). A preliminary study in Jember Regency stated that 21 out of 30 students had been victims of cyberbullying. Purpose: To find out the correlation between parental interaction (the role of monitoring online activity, disciplining and potential conflict) and exposure to cyberbullying (flamming, harassment, denigrations, impersonations, outing, exclusion, cyberstalking) on psychological impact (self-confidence, anxiety, hopelessness and suicidal intent) of high school youth in Sumbersari District, Jember Regency. Methods: This is a quantitative research that was conducted at 12 Senior High Schools at Sumbersari District, Jember with a total population of 5,346 students. Simple random sampling research, of 358 Lemeshow sampling students. Collecting interview data and filling out a questionnaire forJanuary 2019. Analysis of chi-square bivariate test data. Results: The significance of parental interaction was found related to conflict with the level of self-confidence and anxiety of adolescents (p 0.00; OR 2.77 and p 0.02; OR 1.71). Interestingly, it was found that harassment had an impact on the level of self-confidence (p 0.00; OR 2.29), anxiety (p 0.00; OR 1.92), hopelessness (p 0.00; OR 2.91) and intention to commit suicide (p 0.02; OR 1.84). Cyberstalking had an impact on the level of self-confidence (p 0.00; OR: 3.02), anxiety (p 0.00; OR: 1.81), hopelessness (p 0.00; OR: 5.50) and intention to suicide (p 0.00; OR: 2.44). Conclusion: Parental interactions and exposure to cyberbullying have a significant effect and play an important role in the psychological impact experienced in adolescence.